THE DIFFERENCE OF MODELS OF ENTREPRENEURSHIP INTENTION BETWEEN STUDENTS OF ECONOMIC AND BUSINESS FACULTY OF MERCU BUANA UNIVERSITY AND FACULTY OF ECONOMICS AND COMMUNICATION OF BINA NUSANTARA UNIVERSITY (COMPARATIVE STUDY) - Aima, M. Havidz; Suta Achmad Wijaya (Dinasti International Journal of Digital Business Management, 2020)
Indonesia's labor conditions still need serious attention. There are still many unemployed people who are actually dominated by educated circles. The high unemployment rate is also due to the large number of college graduates who want to find job rather than those who can create their own jobs by becoming entrepreneurs. There are many factors that influence the decision of students / alumni to start a business or entrepreneurship. One of program in reducing unemployment and increasing employment is entrepreneurship education. Mercu Buana University and Bina Nusantara University are among the tertiary institutions in Indonesia that provide entrepreneurship education. This study aims to determine the effect of internal and external factors on entrepreneurship intention mediated by entrepreneurship cognition at Mercu Buana University and Bina Nusantara University. This study uses a quantitative approach with data analysis in testing the measurement model and testing the structural model using SmartPLS software version 3.2.7. The results of the study can show that internal factors and external factors have a significant positive effect on entrepreneurship cognition and entrepreneurship intention in Mercu Buana University and Bina Nusantara University, if internal factors and external factors are mediated by entrepreneurship cognition variable, the effect becomes significant on entrepreneurship intention. In addition, entrepreneurship cognition also has a significant positive effect on entrepreneurship intention in Mercu Buana University and Bina Nusantara University